Optimization of The Function of the Prosecutor's Office in the Return Of State Financial Losses Due to Corruption (Case Study At the Wajo District Prosecutor's Office) - -, Renaldi; Mas, Marwan; Siku, Abdul Salam (Indonesian Journal of Legality of Law, 2018)
This study aims to find out the efforts made by the Wajo District Attorney in recovering state financial losses due to corruption and the constraints faced by the Wajo District Attorney in recovering state financial losses due to corruption. This research was conducted using normative (legal research) and sociological juridical (Socio Legal Research) methods by interviewing a number of respondents with purposive sampling method with face to face interview interviews using a sampling technique using a combination of qualitative analysis that produced analytical descriptive data, namely what the respondent stated verbally or in writing. The results showed that the Prosecutor's Office carried out its function in eradicating corruption, especially regarding the return of losses on state finances carried out through penal and non-penal means, namely the investigation, prosecution and execution of court decisions, and non-judgments through a civil approach. In the practice of the ideal role of the Attorney General's Office in an effort to recover state financial losses due to Criminal Acts Corruption has not run optimally due to constraints both technical, juridical and other constraints. In tracing and discovering assets / assets of suspects, defendants or convicted persons for confiscation (as part of the investigation and as a court decision). Prosecutors and prosecutors executors have doubts about which objects belonging to suspects, defendants or convicts can be confiscated, whether confiscation of all assets can be confiscated or limited to the suspect's assets, other than that falsified or omitted documents also become the main obstacle is the prosecutor's office in the process of eradicating the Corruption Crimes, especially regarding the return of state financial losses.